MEDIAN LETHAL CONCENTRATION (LC50) EKSTRAK DAUN SIRSAK (Annona muricata Linn) TERHADAP LARVA Culex sp DI KOTA KUPANG - Kewa, Maria Magdalena; Almet, Julianty; Laut, Meity Marviana (JURNAL KAJIAN VETERINER, 2020)
The Culex mosquito is a species that can creates health problems for humans and animals. The handling efforts of the vector is very important to reduce the impact caused by this vector. One of the plants that has the potential as a larvicide is soursop leaves (Annona muricata L.). This study aims to determine the effect of soursop leaves (Annona muricata L.) extract on the mortality of Culex sp larvae and LC50 value to killing 50% Culex sp larva. The study was conducted from March to June 2020. This study used 7 treatment groups which 5 groups tested the effectiveness of soursop leaves extract and 2 control groups. The research data was analyzed using the Probit test to determine the LC50. The results showed that soursop leaves extract (Annona muricata L.) was effective in killing Culex sp larvae with LC50 value is 0.736%.